A COMPARATIVE TYPOLOGICAL STUDY OF THE IMAGE OF THE HORSE IN WORLD AND UZBEK LITERATURE - Mansurova Shohista Ismailovna (International Scientific and Current Research Conferences, 2025)
This comparative study examines the horse’s portrayal in global and Uzbek literatures, revealing shared qualities, cultural contexts, and deep spiritual resonances that underscore humanity’s enduring fascination with these noble companions.